(untitled) (Global Journal of Human-Social Science, 2013)
In contrast to recent general conceptions of technical secondary schools in Ontario, the Windsor Walkerville Technical School, later named W.D. Lowe Technical School, was wholeheartedly supported by its community. The school began with a vision of offering education that was appealing to those boys who were deemed likely to end up in "gangs of hooligans." The rough and tough reputation of the WWTS/WDLTS would attest to the needs that founder F.P. Gavin saw in the community, but the school quickly gained a reputation for turning out the "captains and generals" of the industrial army in the form of skilled and successful machinists, tool and die makers and mould makers who built specialized parts for the automotive industry. The school existed historically in a social and economic context with the ingredients for a technical secondary school that served working class male youth well. Today those ingredients no longer exist.